Mastitis - Fazilet Erözgen; Mehmet Celal Kızılkaya; Gamze Çıtlak (Haseki Tıp Bülteni)
Mastitis is an infectious or non-infectious breast disease associated with breast inflammation. It is observed most frequently during milk stasis (engorgement) and lactation period (puerperal) with superimposed infection. Most mastitides heal with simple self-help measures, however, sometimes antibiotherapy and abscess drainage may be required. Other than lactating period, mastitides are encountered in the presence of recurrent infections and abscess. Although various factors, such as smoking, diabetes, rheumatoid arthritis can at times be the root causes of mastitis, they are frequently observed in granulomatous mastitides. Treatment approaches not involving biopsy are disadvantageous and harmful in such cases which can be confused with breast cancer. Ultrasound-guided abscess drainage in patients with breast abscess and irrigation of the pouch with saline are the preferred treatment approach today. (The Medical Bulletin of Haseki 2014; 52: 150-2)